Team-Based Learning: Cavernous Sinus Thrombosis - Kurt Gilliland; Edward Kernick (Association of American Medical Colleges, 2014)
Abstract With four incremental releases of information, this team-based learning case challenges students to diagnose cavernous sinus thrombosis and understand its mechanism while also evaluating symptoms of eye movement. This team-based learning exercise has been used for five years in the course. Initially, the exercise was conducted as a series of online blog-style releases, with students in four-person groups logging into private forums to discuss the details of the case. In the last two years, it has been conducted in a 90-minute small-group setting with six person groups working on parts of the case in rooms of 36 students, each with 2 instructors. Overall, there were 5 rooms of 36 students each. Course feedback and examination analysis shows proficiency in the trigeminal nerve, dural venous sinuses, and eye testing.